Nothing about Us without Us: Role of Patient and Public Involvement in Health Research in Pakistan - Muhammad Adnan; Muhammad Kashif Munir (Pakistan Journal of Medical Research)
Patient and Public Involvement (PPI) emphasizes on including patients and the public in shaping health research, aligning with the principle "Nothing about us without us." It transforms patients from passive subjects into active collaborators, allowing their lived experiences to inform research that is more relevant and effective.1 Globally, PPI fosters transparency, inclusivity, and ethical practices, helping align healthcare solutions with real-world needs.2  In Pakistan, PPI is in its infancy but has the potential to make healthcare more equitable and responsive. Implementing PPI in Pakistan faces significant challenges. Public and researchers alike often lack awareness about its importance and practices.3 Financial constraints and inadequate infrastructure further hinder progress, while traditional hierarchical structures in research limit genuine collaboration. These barriers highlight the need for targeted strategies to promote PPI in Pakistan's healthcare system.4